2014
DOI: 10.1115/1.4026039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamics and Soret Effects on Bioconvection in a Porous Medium Saturated With a Nanofluid Containing Gyrotactic Microorganisms

Abstract: We investigate the bioconvection of gyrotactic microorganism near the boundaiy layer region of an inclined semi infinite permeable plate embedded in a porous medium filled with a water-based nanofluid containing motile microorganisms. The model for the nanofluid incorporates Brownian motion, thermophoresis, also Soret effect and magnetic field effect are considered in the study. The governing partial differential equations for momentum, heat, solute concentration, nanoparticle volume fraction, and microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…One of the effective mechanisms that control convective instability is that of maintaining a nonlinear temperature gradient. Recently, considering various convective flow models in porous medium [5][6][7], fluid layer [8][9][10] the phenomenon of heat or mass transfer investigated, where the concept of regulating either heat or mass transfer is missing. The temperature gradient can be achieved by time-dependent heating or cooling at the boundaries, the related problems have been investigated by Nield [11], Chhuon and Caltagirone [12], Rudraiah et al [13], Rudraiah and Malashetty [14], Caltagirone [15], Bhatia and Bhadauria [16,17], Bhadauria [18][19][20][21][22][23][24], Bhadauria and Suthar [25], Bhadauria and Srivastava [26], Bhadauria et al [27], Bhadauria and Kiran [28,29] and Kiran and Bhadauria [30].…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective mechanisms that control convective instability is that of maintaining a nonlinear temperature gradient. Recently, considering various convective flow models in porous medium [5][6][7], fluid layer [8][9][10] the phenomenon of heat or mass transfer investigated, where the concept of regulating either heat or mass transfer is missing. The temperature gradient can be achieved by time-dependent heating or cooling at the boundaries, the related problems have been investigated by Nield [11], Chhuon and Caltagirone [12], Rudraiah et al [13], Rudraiah and Malashetty [14], Caltagirone [15], Bhatia and Bhadauria [16,17], Bhadauria [18][19][20][21][22][23][24], Bhadauria and Suthar [25], Bhadauria and Srivastava [26], Bhadauria et al [27], Bhadauria and Kiran [28,29] and Kiran and Bhadauria [30].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study of the MHD nonNewtonian nanofluids over a cone [9], Raju and Sandeep [10] did a comparative research and found that the heat and mass transfer in MHD non-Newtonian bioconvection flow over a rotating cone was significantly high when compared with the flow over a rotating plate. Other researchers have done several work related to the bioconvection, such as the MHD stagnation point flow of gyrotactic microorganisms [11,12], the unsteady mixed bioconvection flow [13,14] and the bioconvection in porous medium [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Resilient microorganisms swimming upwards maintain this bioconvection pattern [1][2][3]. Several studies have been conducted to explain the mechanism of directional motion of the different types of microorganisms [4][5][6][7]. It has been found that the resultant large-scale motion of fluid containing self-propelling motile microorganisms enhances mixing, preventing nanoparticle agglomeration in nanofluids [8][9][10].…”
Section: Introductionmentioning
confidence: 99%